1998
DOI: 10.1070/qe1998v028n10abeh001345
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the refractive index of an Nd:YAG laser crystal on excitation of the Nd3+ions

Abstract: A polarising interferometer was used to investigate changes in the refractive index of an Nd : YAG laser crystal associated with changes in the populations of the electronic energy levels characterised by different polarisabilities. The study was carried out on diode-pumped crystals as well as on crystals which were flashlamp-pumped under conditions of saturation of the gain experienced by the optical beam. The changes in the refractive index depended nonlinearly on the pump power. The ratio of the real and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…8 Moreover, the 13 C NMR resonances at 187.8 ppm can be unequivocally attributed to the coordinated aromatic sandwich carbons shifted with respect to signal for the free aromatic ligands. 8 The 13 C NMR resonances at 14-17 ppm are assinged to the methyl carbons in the aromatic ring ethyl substituent. EXAFS analysis confirms that the chromium is present only in the form of the bis-arene complex.…”
Section: Synthesis Of Polymer-precursors and Their Spectral Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Moreover, the 13 C NMR resonances at 187.8 ppm can be unequivocally attributed to the coordinated aromatic sandwich carbons shifted with respect to signal for the free aromatic ligands. 8 The 13 C NMR resonances at 14-17 ppm are assinged to the methyl carbons in the aromatic ring ethyl substituent. EXAFS analysis confirms that the chromium is present only in the form of the bis-arene complex.…”
Section: Synthesis Of Polymer-precursors and Their Spectral Propertiesmentioning
confidence: 99%
“…This method (Fig. 14) has been used to study the excited states of pumped Nd:YAG crystals, 13 small absorptions in optical materials in the middle infrared frequency band, 14,15 and the measurement of heavy metal concentrations in water. 16 The polymer films were gripped between two glass-plates coated with a tin oxide electrically-conducting layer.…”
Section: Electro-optic Coefficient Measurementsmentioning
confidence: 99%
“…(i) heating an active fiber due to the energy exchange between pump and lasing photons and also due to absorption and scattering of the radiation in the active medium and polymer coating [6,7]; and (ii) change of an active medium polarization due to change in the population of laser levels [4,[8][9][10].…”
Section: Mechanisms Of Refractive Index Change In Active Optical Fibementioning
confidence: 99%
“…This effect has been investigated for injection lasers; however, it is evident that the data obtained are general in character and can be used for other solid-state lasers. For example, the calculation simulation of an analogous self-modulation process in Nd:YAG lasers with lasing and nonlinear parameters used in [9] has shown that the regime of nanosecond relaxation self-pulsations can be realized in these lasers. A significant factor favorable for the appearance of regular pulsations at a constant pumping level is the self-modulation broadening of the amplification line.…”
Section: Introductionmentioning
confidence: 98%
“…In the case of a complex profile of the amplification band, even the detuning of the maximum lasing frequency from the fundamental frequency of the active transition can be nonzero. It has been established in [8,9] that the refractive index of semiconductors and activated crystals changes resonantly depending on the magnitude and sign of such a detuning. Under these conditions, the dynamics of laser radiation depends on the self-modulation broadening of the amplification line and on the relation between the amplitude and phase of the radiation pulses.…”
mentioning
confidence: 99%